Fiber / aerogel composite thermal insulation material

By combining modified glass fiber with sol, the dynamic imimium bonds and quaternary ammonium salt groups in the modified silane coupling agent are solved, and the problem of insufficient antibacterial properties and mechanical properties of fiber/aerogel composites is achieved. It has better self-repair and thermal insulation performance, and improves the overall performance of the material.

CN119306466APending Publication Date: 2025-01-14吉祥三宝高科新材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411428175.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The poor antibacterial properties of existing fiber/aerogel composites have led to certain shortcomings in their applications.

Method used

By combining modified glass fibers with sols, the dynamic imimy bonds, quaternary ammonium groups and long-chain alkyl groups in the modified silane coupling agent are used to improve the self-healing, antibacterial and hydrophobic properties of the composite material, and through modification The silane coupling agent forms covalent bonds with the polycondensation of hydroxyl groups on the surface of glass fibers, enhancing the mechanical properties and interface compatibility of the material.

Benefits of technology

The self-healing ability, antibacteriality, hydrophobicity and mechanical properties of fiber/aerogel composites are significantly improved, and the comprehensive performance is better than the existing technology and has a wider range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082779580000101
    Figure BDA0005082779580000101
  • Figure BDA0005082779580000111
    Figure BDA0005082779580000111
Patent Text Reader

Abstract

The invention discloses a fiber / aerogel composite thermal insulation material, and belongs to the technical field of thermal insulation materials, the fiber / aerogel composite thermal insulation material provided by the invention comprises the following raw materials by mass fraction: 75-90% of sol and 10-25% of modified glass fiber. The preparation method of the fiber / aerogel composite thermal insulation material comprises the following steps: step A1, mixing tetraethoxysilane and an ethanol water solution, adjusting the pH value to 2-3, stirring at 50 DEG C for 0.5-1 hour, and adjusting the pH value to 6.9-7.3 to obtain sol; a2, pouring the sol into a mold containing modified glass fibers, sealing and standing to obtain gel, and treating at 60-80 DEG C for 10-15 hours; and taking out the product, replacing the solvent, and drying to obtain the fiber / aerogel composite thermal insulation material. The prepared composite material has excellent comprehensive performance and is wide in application field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation materials, and in particular relates to a fiber / aerogel composite thermal insulation material. Background Art

[0002] Among the many types of aerogels, SiO2 aerogel is the earliest aerogel to be developed and commercialized. It is widely used in the field of thermal insulation because of its extremely low density and low thermal conductivity. However, due to the high porosity and low density of pure SiO2 aerogel, its mechanical properties are poor and it is prone to brittle breakage when squeezed by external forces. To solve this problem, researchers introduced a composite combination of SiO2 aerogel and fiber materials. This technological breakthrough not only effectively retains the original low thermal conductivity advantage of SiO2 aerogel, but also significantly enhances the toughness and mechanical strength of the material, achieving a leap in performance. Currently, the more common SiO2 aerogel composite cotton felt fiber categories include ceramic fiber, glass fiber, polypropylene fiber, and carbon fiber.

[0003] Patent CN108641361 B discloses a fiber-reinforced silicone aerogel thermal insulation composite material and its preparation method. The composite material obtained in this patent is based on a siloxane polymer with a porous structure as a matrix and a flexible fiber felt as a reinforcement. It is prepared by preparing an organic silicone solution, impregnating the flexible fiber felt with the solution, a sol-gel process, washing-drying, etc. However, the fiber / aerogel composite material prepared by this patent and the prior art still has the problem of poor antibacterial properties and other performance issues. Summary of the invention

[0004] In order to solve the problem that the fiber / aerogel composite materials prepared by the prior art still have poor performance such as antibacterial properties, the purpose of the present invention is to provide a fiber / aerogel composite thermal insulation material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A fiber / aerogel composite heat-insulating and warm-keeping material comprises the following raw materials: sol with a mass fraction of 75-90% and modified glass fiber with a mass fraction of 10-25%.

[0007] A fiber / aerogel composite thermal insulation material, the preparation method of which comprises the following steps:

[0008] Step A1: After mixing ethyl orthosilicate and ethanol aqueous solution, add 3% by volume of hydrofluoric acid to adjust the pH to 2-3, stir in a 50° C. water bath for 0.5-1 h, add 25wt% ammonia water to adjust the pH to 6.9-7.3, and obtain a sol;

[0009] The dosage ratio of ethyl orthosilicate and ethanol aqueous solution is 20.8 g:80-90 mL; the volume ratio of anhydrous ethanol and deionized water in the ethanol aqueous solution is 1.2:1.

[0010] Step A2: pour the sol into a mold containing modified glass fiber, seal and let gel stand, and treat at 60-80°C for 10-15h; take out the product and replace it with methanol 3 times, each time with an interval of 12h, then place it in an oven at 50°C for 12h, and then place it in an oven at 80°C for 2h to obtain a fiber / aerogel composite thermal insulation material.

[0011] Furthermore, the preparation method of the modified glass fiber is:

[0012] Step B1: soak the glass fiber in acetone for 24 hours to remove surface oil, then wash it with distilled water for 4 times, and dry it at 100° C. for 2 hours to obtain pretreated glass fiber;

[0013] Among them, the usage ratio of glass fiber to acetone is 30g:1.5L.

[0014] Step B2: placing the pretreated glass fiber into a modified silane coupling agent solution, stirring at room temperature for 5-6 hours, filtering out, and drying at 80° C. for 3-4 hours to obtain a modified glass fiber;

[0015] The dosage ratio of the pretreated glass fiber to the modified silane coupling agent solution is 100g:150-200mL; the dosage ratio of the modified silane coupling agent to the 90% ethanol aqueous solution by volume in the modified silane coupling agent solution is 5-7g:100mL.

[0016] Furthermore, the preparation method of the modified silane coupling agent is:

[0017] Step C1: dissolving triethoxysilyl undecanealdehyde and N,N-dimethylethylenediamine in anhydrous ethanol, reacting at 20-30° C. for 20-30 min, filtering, and drying to obtain a silane coupling agent containing an imine bond;

[0018] Among them, the usage ratio of triethoxysilyl undecanealdehyde, N,N-dimethylethylenediamine and anhydrous ethanol is 33.3g:8.8g:400-450mL.

[0019] In the above steps, the aldehyde group of triethoxysilyl undecanealdehyde and the amine group of N,N-dimethylethylenediamine form a dynamic imine bond through an aldehyde-amine condensation reaction.

[0020] Step C2: Mix the silane coupling agent containing an imine bond, dodecane bromide and isopropanol, raise the temperature to 80° C., react for 8 hours, and then distill under reduced pressure to obtain a modified silane coupling agent.

[0021] The usage ratio of the silane coupling agent containing an imine bond, dodecane bromide and isopropanol is 6.3 g:4.1 g:40-50 mL.

[0022] In the above steps, the silane coupling agent containing an imino bond undergoes a quaternization reaction with dodecane bromide to obtain a modified silane coupling agent, thereby introducing a quaternary ammonium salt group and a long-chain alkyl group into the silane coupling agent containing an imino bond.

[0023] Through the above two-step reaction, dynamic imine bonds, quaternary ammonium salt groups, and long-chain alkyl groups are introduced into the modified silane coupling agent. After the glass fiber is modified by the modified silane coupling agent and subjected to a sol-gel reaction with the sol, a fiber / aerogel composite thermal insulation material containing dynamic imine bonds, quaternary ammonium salt groups, and long-chain alkyl groups can be obtained. The imine bond is a dynamic covalent carbon-nitrogen double bond that is reversible at room temperature. The self-repair process of the imine bond is a dynamic equilibrium process. Inside the material, the breaking and recombination of the imine bond are constantly carried out, so that the material can self-repair to a certain extent and maintain its integrity and performance. Combining the modified glass fiber containing the imine bond with the sol can improve the self-repair performance of the composite material; the quaternary ammonium salt group and the long-chain alkyl group have excellent antibacterial and hydrophobic properties. Combining the modified glass fiber containing the quaternary ammonium salt group and the long-chain alkyl group with the sol can improve the antibacterial and hydrophobic properties of the composite material.

[0024] Furthermore, the present invention modifies the glass fiber by using a modified silane coupling agent, and the hydroxyl groups generated by the hydrolysis of the modified silane coupling agent can form covalent bonds with the hydroxyl groups on the surface of the glass fiber by condensation, so that the modified silane coupling agent is grafted onto the surface of the glass fiber, and the modified silane coupling agent contains a long-chain alkyl group, which is a flexible carbon chain that can toughen the sol, thereby improving the mechanical properties of the fiber / aerogel composite material. At the same time, the interface compatibility between the glass fiber modified by the modified silane coupling agent and the sol is enhanced, forming a denser structure, thereby reducing air heat convection and improving the thermal insulation and warmth performance of the composite material.

[0025] Beneficial effects of the present invention:

[0026] The fiber / aerogel composite thermal insulation material prepared by combining modified glass fiber with sol in the present invention has excellent self-repairing ability, antibacterial property, hydrophobicity, mechanical property and thermal insulation performance. Compared with the fiber / aerogel composite thermal insulation material prepared by the prior art, it has better comprehensive performance and wider application field. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The glass fibers in the present invention were purchased from Shaanxi Huate Fiberglass Materials Co., Ltd.

[0029] Example 1

[0030] The preparation method of the modified silane coupling agent of this embodiment is:

[0031] Step C1: 33.3 g of triethoxysilyl undecanealdehyde and 8.8 g of N,N-dimethylethylenediamine were dissolved in 450 mL of anhydrous ethanol, reacted at 20° C. for 20 min, filtered, and dried to obtain a silane coupling agent containing an imino bond;

[0032] Step C2: 6.3 g of an imine bond-containing silane coupling agent, 4.1 g of bromododecane, and 50 mL of isopropanol were mixed, the temperature was raised to 80° C., the mixture was reacted for 8 h, and then the mixture was distilled under reduced pressure to obtain a modified silane coupling agent.

[0033] Example 2

[0034] The preparation method of the modified silane coupling agent of this embodiment is:

[0035] Step C1: 33.3 g of triethoxysilyl undecanealdehyde and 8.8 g of N,N-dimethylethylenediamine were dissolved in 420 mL of anhydrous ethanol, reacted at 25° C. for 25 min, filtered, and dried to obtain a silane coupling agent containing an imine bond;

[0036] Step C2: 6.3 g of an imine bond-containing silane coupling agent, 4.1 g of bromododecane, and 45 mL of isopropanol were mixed, the temperature was raised to 80° C., the mixture was reacted for 8 h, and then the mixture was distilled under reduced pressure to obtain a modified silane coupling agent.

[0037] Example 3

[0038] The preparation method of the modified silane coupling agent of this embodiment is:

[0039] Step C1: 33.3 g of triethoxysilyl undecanealdehyde and 8.8 g of N,N-dimethylethylenediamine were dissolved in 400 mL of anhydrous ethanol, reacted at 30° C. for 30 min, filtered, and dried to obtain a silane coupling agent containing an imino bond;

[0040] Step C2: 6.3 g of an imine bond-containing silane coupling agent, 4.1 g of bromododecane, and 40 mL of isopropanol were mixed, the temperature was raised to 80° C., the mixture was reacted for 8 h, and then the mixture was distilled under reduced pressure to obtain a modified silane coupling agent.

[0041] Comparative Example 1

[0042] The preparation method of the modified silane coupling agent of this comparative example is:

[0043] Step C1: dissolving 23.4 g of triethoxysilyl butyraldehyde and 8.8 g of N,N-dimethylethylenediamine in 450 mL of anhydrous ethanol, reacting at 30° C. for 30 min, filtering, and drying to obtain a silane coupling agent containing an imino bond;

[0044] Step C2: 4.6 g of an imine bond-containing silane coupling agent, 4.1 g of bromododecane, and 50 mL of isopropanol were mixed, the temperature was raised to 80° C., the mixture was reacted for 8 h, and then the mixture was distilled under reduced pressure to obtain a modified silane coupling agent.

[0045] Comparative Example 2

[0046] The preparation method of the modified silane coupling agent of this comparative example is:

[0047] Step C1: 33.3 g of triethoxysilyl undecanealdehyde and 8.8 g of N,N-dimethylethylenediamine were dissolved in 450 mL of anhydrous ethanol, reacted at 20° C. for 20 min, filtered, and dried to obtain a silane coupling agent containing an imino bond;

[0048] Step C2: 6.3 g of an imine bond-containing silane coupling agent, 2.7 g of bromohexane, and 50 mL of isopropanol were mixed, the temperature was raised to 80° C., the mixture was reacted for 8 h, and then the mixture was distilled under reduced pressure to obtain a modified silane coupling agent.

[0049] Comparative Example 3

[0050] The preparation method of the modified silane coupling agent of this comparative example is:

[0051] 33.3 g of triethoxysilyl undecanealdehyde and 8.8 g of N,N-dimethylethylenediamine were dissolved in 450 mL of anhydrous ethanol, reacted at 20° C. for 20 min, filtered, and dried to obtain a modified silane coupling agent.

[0052] Comparative Example 4

[0053] In this comparative example, the modified silane coupling agent is directly replaced by triethoxysilyl undecanedialdehyde.

[0054] Example 4

[0055] The preparation method of the modified glass fiber of this embodiment is:

[0056] Step B1: 30 g of glass fiber was immersed in 1.5 L of acetone for 24 h to remove surface oil, then washed with distilled water for 4 times, and dried at 100 °C for 2 h to obtain pretreated glass fiber;

[0057] Step B2: Place 100 g of pretreated glass fiber into 150 mL of modified silane coupling agent solution (the ratio of modified silane coupling agent to 90% ethanol aqueous solution by volume is 5 g:100 mL), stir at room temperature for 5 h, filter out, and dry at 80° C. for 3 h to obtain modified glass fiber.

[0058] The preparation method of the modified silane coupling agent is the same as that of Example 1.

[0059] Example 5

[0060] The preparation method of the modified glass fiber of this embodiment is:

[0061] Step B1: 30 g of glass fiber was immersed in 1.5 L of acetone for 24 h to remove surface oil, then washed with distilled water for 4 times, and dried at 100 °C for 2 h to obtain pretreated glass fiber;

[0062] Step B2: Place 100 g of pretreated glass fiber into 170 mL of modified silane coupling agent solution (the ratio of modified silane coupling agent to 90% ethanol aqueous solution by volume is 6 g:100 mL), stir at room temperature for 5.5 h, filter out, and dry at 80° C. for 3.5 h to obtain modified glass fiber.

[0063] The preparation method of the modified silane coupling agent is the same as that in Example 2.

[0064] Example 6

[0065] The preparation method of the modified glass fiber of this embodiment is:

[0066] Step B1: 30 g of glass fiber was immersed in 1.5 L of acetone for 24 h to remove surface oil, then washed with distilled water for 4 times, and dried at 100 °C for 2 h to obtain pretreated glass fiber;

[0067] Step B2: Place 100 g of pretreated glass fiber into 200 mL of modified silane coupling agent solution (the ratio of modified silane coupling agent to 90% ethanol aqueous solution by volume is 7 g:100 mL), stir at room temperature for 6 h, filter out, and dry at 80° C. for 4 h to obtain modified glass fiber.

[0068] The preparation method of the modified silane coupling agent is the same as that in Example 3.

[0069] Comparative Example 5

[0070] This comparative example provides a modified glass fiber. Compared with Example 4, the difference is that the modified silane coupling agent in Example 4 is replaced by the modified silane coupling agent prepared in Comparative Example 1, and the remaining raw materials and steps are the same as Example 4.

[0071] Comparative Example 6

[0072] This comparative example provides a modified glass fiber. Compared with Example 4, the difference is that the modified silane coupling agent in Example 4 is replaced by the modified silane coupling agent prepared in Comparative Example 2, and the remaining raw materials and steps are the same as Example 4.

[0073] Comparative Example 7

[0074] This comparative example provides a modified glass fiber. Compared with Example 4, the difference is that the modified silane coupling agent in Example 4 is replaced by the modified silane coupling agent prepared in Comparative Example 3, and the remaining raw materials and steps are the same as Example 4.

[0075] Comparative Example 8

[0076] This comparative example provides a modified glass fiber. Compared with Example 4, the difference is that the modified silane coupling agent in Example 4 is replaced by the modified silane coupling agent prepared in Comparative Example 4, and the remaining raw materials and steps are the same as Example 4.

[0077] Example 7

[0078] The present embodiment provides a fiber / aerogel composite thermal insulation material, comprising the following raw materials: 90% by mass of a sol, and 10% by mass of the modified glass fiber prepared in Example 4.

[0079] The preparation steps of a fiber / aerogel composite thermal insulation material are as follows:

[0080] Step A1: 20.8 g of tetraethyl orthosilicate and 80 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 1.2:1) are mixed, and then 3% by volume of hydrofluoric acid is added to adjust the pH to 2-3. After stirring in a 50° C. water bath for 0.5 h, 25 wt % of ammonia water is added to adjust the pH to 6.9-7.3 to obtain a sol;

[0081] Step A2: Pour the sol into a mold containing modified glass fiber, seal and let the gel stand, and treat it at 60°C for 10 hours; take out the product and replace it with methanol three times, each time with an interval of 12 hours, then place it in an oven at 50°C for 12 hours, and then place it in an oven at 80°C for 2 hours to obtain a fiber / aerogel composite thermal insulation material.

[0082] Example 8

[0083] The present embodiment provides a fiber / aerogel composite thermal insulation material, comprising the following raw materials: 85% by mass of sol, and 15% by mass of the modified glass fiber prepared in Example 5.

[0084] The preparation steps of a fiber / aerogel composite thermal insulation material are as follows:

[0085] Step A1: 20.8 g of tetraethyl orthosilicate and 80 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 1.2:1) are mixed, and then 3% by volume of hydrofluoric acid is added to adjust the pH to 2-3. After stirring in a 50° C. water bath for 0.5 h, 25 wt % of ammonia water is added to adjust the pH to 6.9-7.3 to obtain a sol;

[0086] Step A2: Pour the sol into a mold containing modified glass fiber, seal and let the gel stand, and treat it at 70°C for 12 hours; take out the product and replace it with methanol three times, each time with an interval of 12 hours, then place it in an oven at 50°C for 12 hours, and then place it in an oven at 80°C for 2 hours to obtain a fiber / aerogel composite thermal insulation material.

[0087] Example 9

[0088] The present embodiment provides a fiber / aerogel composite thermal insulation material, comprising the following raw materials: 75% by mass of a sol, and 25% by mass of the modified glass fiber prepared in Example 6.

[0089] The preparation steps of a fiber / aerogel composite thermal insulation material are as follows:

[0090] Step A1: 20.8 g of tetraethyl orthosilicate and 80 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 1.2:1) are mixed, and then 3% by volume of hydrofluoric acid is added to adjust the pH to 2-3. After stirring in a 50° C. water bath for 0.5 h, 25 wt % of ammonia water is added to adjust the pH to 6.9-7.3 to obtain a sol;

[0091] Step A2: Pour the sol into a mold containing modified glass fiber, seal and let the gel stand, and treat it at 80°C for 15 hours; take out the product and replace it with methanol three times, each time with an interval of 12 hours, then place it in an oven at 50°C for 12 hours, and then place it in an oven at 80°C for 2 hours to obtain a fiber / aerogel composite thermal insulation material.

[0092] Comparative Example 9

[0093] A fiber / aerogel composite thermal insulation material, compared with Example 7, the difference is that the modified glass fiber in Example 7 is replaced by the product prepared in Comparative Example 5, and the other raw materials, processes and parameters are the same as Example 7.

[0094] Comparative Example 10

[0095] A fiber / aerogel composite thermal insulation material, compared with Example 7, the difference is that the modified glass fiber in Example 7 is replaced by the product prepared in Comparative Example 6, and the other raw materials, processes and parameters are the same as Example 7.

[0096] Comparative Example 11

[0097] A fiber / aerogel composite thermal insulation material, compared with Example 7, the difference is that the modified glass fiber in Example 7 is replaced by the product prepared in Comparative Example 7, and the other raw materials, processes and parameters are the same as Example 7.

[0098] Comparative Example 12

[0099] A fiber / aerogel composite thermal insulation material, compared with Example 7, the difference is that the modified glass fiber in Example 7 is replaced by the product prepared in Comparative Example 8, and the other raw materials, processes and parameters are the same as Example 7.

[0100] The fiber / aerogel composite thermal insulation materials prepared in Examples 7 to 9 and Comparative Examples 9 to 12 were subjected to performance tests. The test items are as follows. The specific test results are shown in Table 1:

[0101] (1) Hydrophobicity test: The contact angle of deionized water was tested using a contact angle tester according to the method of GB / T 30693-2014 "Measurement of the contact angle of plastic film with water". The average value of the test was taken as the calculation result after 5 consecutive tests.

[0102] (2) Antibacterial test: LB solid medium was selected to culture Escherichia coli. The bacteria were inoculated on an agar medium. After the Escherichia coli was spread, a 6 mm diameter disc of the fiber / aerogel composite thermal insulation material prepared in Example 7-Example 9 and Comparative Example 9-Comparative Example 12 was placed on the medium. The material was cultured in a 37°C biochemical incubator for 24 hours, and the size of the inhibition zone was observed.

[0103] (3) Mechanical properties test: The longitudinal (length direction) and transverse (width direction) tensile strength of the glass fiber aerogel felt were tested using a material mechanical properties testing machine. The tensile test rate was 5 mm / min and the sample width was 25 mm.

[0104] (4) Thermal insulation performance test: The thermal conductivity of the sample was analyzed using a TC3000E thermal coefficient meter.

[0105] (5) Self-repairing performance: The dumbbell-shaped fiber / aerogel composite thermal insulation materials prepared in Examples 7 to 9 and Comparative Examples 9 to 12 were cut into two halves with a blade, and the two separated parts were immediately contacted and placed under 80% humidity and 25° C. conditions for 24 hours for self-repairing. The tensile strength at break before and after self-healing was measured using a universal material tensile machine, and the self-repair rate was calculated, self-repair rate (%) = tensile strength of the composite material before treatment / tensile strength of the composite material after treatment × 100%.

[0106] Table 1

[0107]

[0108]

[0109] It can be seen from the table that the comprehensive performance of the fiber / aerogel composite thermal insulation materials prepared in Examples 7 to 9 is better than that of the fiber / aerogel composite thermal insulation materials prepared in Comparative Examples 9 to 12. The modified silane coupling agent in the composite material prepared in Comparative Example 9 replaces "triethoxysilyl undecanealdehyde" with "triethoxysilyl butyraldehyde", and the alkyl chain of triethoxysilyl butyraldehyde is shorter, which reduces the overall hydrophobicity and mechanical properties of the composite material; the modified silane coupling agent in the composite material prepared in Comparative Example 10 replaces "bromododecane" with "bromohexane", which is similar to Comparative Example 9. Comparative Example 10 also lacks a part of the long alkyl chain, thereby reducing the overall hydrophobicity and mechanical properties of the composite material, and the hydrophobicity of the composite material prepared in Comparative Example 10 is lower than Comparative Example 9 shows that the long chain alkyl in brominated dodecane plays a key hydrophobic role; the modified silane coupling agent in the composite material prepared in Comparative Example 11 does not contain long-chain alkyl and quaternary ammonium salt groups, so that the antibacterial and hydrophobic properties of the composite material prepared in Comparative Example 11 are poor; in the composite material prepared in Comparative Example 12, triethoxysilyl undecanealdehyde is directly used as a silane coupling agent, and the coupling agent does not contain quaternary ammonium salt groups, dynamic imine bonds and long-chain alkyl of brominated dodecane. The composite material does not have antibacterial properties and self-healing properties, and the hydrophobic properties and mechanical properties are further reduced.

[0110] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A fiber / aerogel composite thermal insulation material, characterized in that: Including the following ingredients: The mass fraction of the sol is 75-90%, and the mass fraction of the modified glass fiber is 10-25%.

2. The fiber / aerogel composite thermal insulation material according to claim 1, characterized in that: The preparation of fiber / aerogel composite thermal insulation material includes the following steps: Step A1: After mixing ethyl orthosilicate and ethanol aqueous solution, add 3% by volume hydrofluoric acid to adjust the pH to 2-3, stir at 50° C. for 0.5-1 h, add 25wt% ammonia water to adjust the pH to 6.9-7.3, and obtain a sol; Step A2: pouring the sol into a mold containing modified glass fiber, sealing and allowing the gel to stand, and treating at 60-80° C. for 10-15 hours; taking out the product, replacing the solvent, and drying to obtain a fiber / aerogel composite thermal insulation material.

3. The fiber / aerogel composite thermal insulation material according to claim 2, characterized in that: In step A1, the usage ratio of ethyl orthosilicate and ethanol aqueous solution is 20.8 g:80-90 mL; the volume ratio of anhydrous ethanol and deionized water in the ethanol aqueous solution is 1.2:

1.

4. The fiber / aerogel composite thermal insulation material according to claim 2, characterized in that: The preparation method of modified glass fiber is: Step B1: soaking the glass fiber in acetone for 24 hours, washing, and drying to obtain pretreated glass fiber; Step B2: Place the pretreated glass fiber into the modified silane coupling agent solution, stir at room temperature for 5-6 hours, filter out, and dry at 80° C. for 3-4 hours to obtain the modified glass fiber.

5. The fiber / aerogel composite thermal insulation material according to claim 4, characterized in that: In step B1, the usage ratio of glass fiber to acetone is 30 g:1.5 L.

6. The fiber / aerogel composite thermal insulation material according to claim 4, characterized in that: In step B2, the amount ratio of the pretreated glass fiber to the modified silane coupling agent solution is 100g:150-200mL; the amount ratio of the modified silane coupling agent to the 90% by volume ethanol aqueous solution in the modified silane coupling agent solution is 5-7g:100mL.

7. The fiber / aerogel composite thermal insulation material according to claim 4, characterized in that: The preparation method of the modified silane coupling agent is: Step C1: dissolving triethoxysilyl undecanealdehyde and N,N-dimethylethylenediamine in anhydrous ethanol, reacting at 20-30° C. for 20-30 min, filtering, and drying to obtain a silane coupling agent containing an imine bond; Step C2: Mix the silane coupling agent containing an imine bond, dodecane bromide and isopropanol, raise the temperature to 80° C., react for 8 hours, and then distill under reduced pressure to obtain a modified silane coupling agent.

8. The fiber / aerogel composite thermal insulation material according to claim 7, characterized in that: In step C1, the usage ratio of triethoxysilyl undecanedialdehyde, N,N-dimethylethylenediamine and anhydrous ethanol is 33.3 g:8.8 g:400-450 mL.

9. The fiber / aerogel composite thermal insulation material according to claim 7, characterized in that: In step C2, the usage ratio of the silane coupling agent containing an imine bond, dodecane bromide, and isopropanol is 6.3 g:4.1 g:40-50 mL.

Citation Information

Patent Citations

  • A fiber-reinforced silicone aerogel thermal insulation composite material and its preparation method

    CN108641361B